Nomenclature and synonymic remarks on two species of Eupterotidae (Lepidoptera) described by Johan Christian Fabricius, and notes on related species - Zolotuhin, Vadim V. (Zootaxa, 2018)
Types of two species of monkey moths (Eupterotidae, Lepidoptera) described by Johan Christian Fabricius were located and are here figured for the first time, and lectotypes are designated for both species. The lectotype of Bombyx hibisci Fabricius 1775 is a male from the Hunterian Museum (Glasgow). The lectotype of Bombyx orientalis Fabricius 1793, originally listed from “Dom. Lund” was found in the Zoological Museum—University of Copenhagen (as temporarily loan from the Zoological Museum of Kiel University) with an old incorrect identification label. Both species are members of the genus Eupterote Hübner, 1820 (so-called Brachytera-lineage).                The following new synonymy can thus be established: Eupterote orientalis (Fabricius, 1793), comb. nov. (= Dreata geminata Walker 1855, syn. nov., syn. corr.; = Eupterote geminata var. hebes Grünberg 1914, syn. nov.; = Dreata anada Moore 1860, syn. nov., = Brachytera phalaenaria C. & R. Felder, 1874, syn. nov., = Eupterote auriflua Moore, 1884, syn. nov.).          The type locality for orientalis originally given as “India orientali” is likely to be Sri Lanka.          The related taxon, Eupterote gardneri Bryk, 1950, stat. nov. is established as valid species (bona species) with the a new synonym, Eupterote bifasciata Kishida, 1994, syn. nov.          Eupterote primularis Moore, 1884 is considered a distinct species native to Central and Southern India.